PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA (Studi Pada Guru SMK Berbudi Gantiwarno Klaten): Universitas Budi Luhur Jakarta - Kalilih, Rohianala Yayan; Anwar, Syaiful (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
This research aims to examine the influence of leadership style, motivation, and work environment on job satisfaction among teachers at Berbudi Gantiwarno Klaten Vocational High School. The sample in this study was selected using Nonprobability Sampling, specifically saturated sampling, with a total of 32 teacher respondents. Data were collected through questionnaires using a Likert scale and processed using Microsoft Excel and SPSS software version 22. The research method used is multiple linear regression. The results of this study indicate that the leadership style variable does not affect job satisfaction, while the motivation and work environment variables have a significant impact on job satisfaction. The findings of this study are expected to improve job satisfaction among teachers at SMK Berbudi Gantiwarno Klaten